The Study Properties (Compressive And Tensile And Wear) For The Composite Materials Hybried - Al-Eabi, Suad Hameed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
This study included prepared samples of epoxy reinforced by the novolac , aluminum , glass powder and epoxy reinforced by aluminum , glass powder and epoxy alone .They are used as reinforced materials of volum fraction amounting 40% . The mechanical properties inclouded ( tensile , compressive and wear) where the wear test inclouded different applied loads (5,10,15) . From the results showed the epoxy reinforced by aluminum and glass powder has higher compressive strength (56.91) Mpa and higher tensile strength (132.2) Mpa .But the epoxy alone has higher wear rate and the epoxy reinforced by aluminum and glass powder which have higher elasticity of modulus from the tensile test (315.7) Mpa